Riesgo de osteoporosis en mujeres adultas del club de madres Zoila Victoria de la Torre de Haya de Liberación Social - Víctor Larco, marzo 2015” - Pereda Villajulca, Zúsel Bettina (2015)
Research work Type II was developed: "Risk of Osteoporosis in adult women of the Mothers Club Zoila Victoria Tower Hague Liberation Social-Victor Larco, March 2015", using the enzymatic colorimetric method according to Trinder and FRAX tool: the research type II developed for it worked with 48 adult women who were applied a consent form and a questionnaire, then proceeding to the sampling of blood and processing it, being read in spectrophotometer at 520 nm, with the following results: 38% of the participants are between 61-70 years, 44% had a weight of 51-60kg, 65% represents the participants with a height of 141-150cm, BMI for 58% of all participating states are an overweight, 67% of participants had a fracture antecdente a family, on the other hand both the consumption of snuff and alcohol represent a 100% do not consume any of the above, 54% of all participating women had fosfatatsa high alkaline values, in connection of this enzyme with age, which were between 61-70 years more and 71 had a percentage of 25 and 23% respectively high concentration. It is concluded that the risk of osteoporosis for participants of this club according to the risk factors studied according to the FRAX herrameinta the risk is moderate, and are also provided the proper guidance to maintain a better quality of life and to reverse this risk .